New university careers for the xxi century - Giudice Baca, Víctor (2014)
University professions as we know them today (2014) should be desapearing around 2025. Emerging Asia is building new powerhouses of knowledge. China, South Korea, Japan and Taiwan have educated more than five million scientists and Engineers in the USA in the last 25 years (1990-2014). University Systems of Industrialized and Emerging Asia Nations will occupy the first place around 2030, the USA system shall be in second place and Europe in third position. Which are the new professions for the next 25 years? (2040) the present research has found 27 new professional fields for the future.